Pilot evaluation of psychometric property of the coach-athlete relationship maintenance questionnaire in Japanese junior tennis players - Kuribayashi, C.; Sato, H. (Japanese Journal of Sport Psychology, 2015)
The purpose of this study was to develop pilot evaluation of psychometric property of the Coach-Athlete Relationship Maintenance Questionnaire (CARM-Q) in Japanese junior tennis players and to examine its reliability and validity. The athlete version of CARM-Q was administered to 240 Japanese junior tennis players with a mean age of 15.7±1.3 years. Results of a confirmatory factor analysis replicated the factor structure found in the original version of the CARM-Q (Rhind and Jowett, 2012). Furthermore, it was suggested that the athlete version of CARM-Q had sufficient reliability and validity. The effects of the combination pattern of the coach-athlete dyad (athlete male/coach male, athlete male/coach female, athlete female/coach male, and athlete female/coach female) were tested via MANOVA using 7 subscales from the CARM-Q. Results revealed that the athlete male/coach female group was higher in Conflict management, Openness, and Motivational than the athlete male/coach male group. Additionally, the athlete female/coach male group revealed higher Motivational than the athlete male/coach male group. Future applications were also discussed regarding the CARM-Q as an assessment of the quality of the coach-athlete relationship in Japanese junior sport settings.